Application opportunity of vehicles-to-grid in Indonesian electrical grid. (February 2019) - Aziz, Muhammad; Huda, Muhammad
Abstract: Electric vehicles (EVs) have gained a massive and global interest, including in Indonesia, due to their beneficial characteristics. However, the increase of EVs also causes several problems, especially the stress to the electrical grid because of their high charging demand. In addition, the lack capability of the grid to balance its supply and demand in Indonesia additionally worsen the condition. Indonesia almost has no sufficient storage (buffer) for electricity which can be dispatched (release and absorb) to balance effectively electrical grid. The controllable charging and discharging behavior of EVs has led to the idea to utilize EVs for supporting the grid. The feasibility of vehicle-to-grid (V2G) in Indonesian electrical grid is evaluated in this study. The evaluated ancillary services include load levelling and frequency regulation.